Effect of bimagrumab on thigh muscle volume and composition in men with casting‐induced atrophy. Issue 5 (14th September 2017) - Rooks, Daniel S.; Laurent, Didier; Praestgaard, Jens; Rasmussen, Scott; Bartlett, Michael; Tankó, László B.
Abstract: Background: Patients experiencing disuse atrophy report acute loss of skeletal muscle mass which subsequently leads to loss of strength and physical capacity. In such patients, especially the elderly, complete recovery remains a challenge even with improved nutrition and resistance exercise. This study aimed to explore the clinical potential of bimagrumab, a human monoclonal antibody targeting the activin type II receptor, for the recovery of skeletal muscle volume from disuse atrophy using an experimental model of lower extremity immobilization. Methods: In this double‐blind, placebo‐controlled trial, healthy young men ( n = 24; mean age, 24.1 years) were placed in a full‐length cast of one of the lower extremities for 2 weeks to induce disuse atrophy. After cast removal, subjects were randomized to receive a single intravenous (i.v.) dose of either bimagrumab 30 mg/kg ( n = 15) or placebo ( n = 9) and were followed for 12 weeks. Changes in thigh muscle volume (TMV) and inter‐muscular adipose tissue (IMAT) and subcutaneous adipose tissue (SCAT) of the thigh, maximum voluntary knee extension strength, and safety were assessed throughout the 12 week study. Results: Casting resulted in an average TMV loss of −4.8% and comparable increases in IMAT and SCAT volumes. Bimagrumab 30 mg/kg i.v. resulted in a rapid increase in TMV at 2 weeks following cast removal and a +5.1% increase above pre‐cast levels at 12 weeks. In comparison, TMV returned to pre‐cast level at 12 weeks (−0.1%) in the placebo group. The increased adiposity of the casted leg was sustained in the placebo group and decreased substantially in the bimagrumab group at Week 12 (IMAT: −6.6%, SCAT: −3.5%). Knee extension strength decreased by 25% in the casted leg for all subjects and returned to pre‐cast levels within 6 weeks after cast removal in both treatment arms. Bimagrumab was well tolerated with no serious or severe adverse events reported during the study. Conclusions: A single dose of bimagrumab 30 mg/kg i.v. safely accelerated the recovery of TMV and reversal of accumulated IMAT following 2 weeks in a joint‐immobilizing cast.